Primary Tupaia javanica Hepatocytes Cultures As In Vitro Replication System for Ape Hepatitis B Viruses - MARYATI SURYA; DIAH ISKANDRIATI; SILMI MARIYA; UUS SAEPULOH; PERMANAWATI PERMANAWATI; DONDIN SAJUTHI; JOKO PAMUNGKAS (Microbiology Indonesia, 2016)
Hepatitis B virus (HBV) is a DNA virus with liver as primary target organ.This virus caused chronic infection that can progress to cirrhosis, liver cancer and even death. In vitro model system of hepatocyte cultures is important and widely used to study a variety aspects of hepatitis B. Development of small animal Tupaia sp. for the in vitro model system is an alternative to the existinghepatocyte cultures. The specific purpose of the studyis to develop Tupaia javanica hepatocytes culture for HBV replication, and in a broader spectrum to answer the need for in vitro model of hepatocytes. Primary T. javanica hepatocytes (PTH) culture was successfully maintained for 14 days to reach 80% confluence, and infection of Javan gibbon HBV (GiHBV) and orangutan HBV (OuHBV) onto the culture on day 15 showed viral replication for up to eight days as measured by polymerase chain reaction (PCR). PCR quantification indicated that the highest copy number of DNA virus was detected onday two anddecreased until day 8 after infection. Cell receptor for HBV attachment, known as sodium taurocholate cotransporting polypeptide was expressed on the surface of PTH and shown as green luminenscent when observed by immunofluorescence assay. Sequence of partialS gene from the apes HBVs after the viruses have been infected to the PTH showed amino acid identity to their wildtype as high as 99.29% for GiHBV and 95.71% for OuHBV. This study suggested that the PTH can support the replication of GiHBV andÂ  OuHBV.Â